Mā Madā Iltizām al-Qiyādāt al-Nisāʾiyyah bi-Mabādiʾ al-Qiyādah al-Islāmiyyah fī Madāris al-Taʿlīm al-ʿĀmm bi-Ṣanaʿāʾ: Dirāsah Waṣfiyyah Taḥlīliyyah - Eman Ahmed Mohammed abdulatef Alshameri; Masyitoh; Saiful Bahri (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines the extent to which female educational leaders in public schools in the Capital Secretariat of Sana’a adhere to the principles of Islamic leadership, the factors motivating their commitment, and the impact of these principles on leadership practices. The study addresses a notable research gap caused by the scarcity of applied studies on female leadership in Yemen from an Islamic leadership perspective, despite women’s expanding roles in school administration. Using a descriptive-analytical approach, data were collected through a questionnaire administered to a sample of female school leaders. Statistical analysis relied on means and standard deviations, with findings interpreted in light of Islamic leadership principles derived from classical religious sources and supported by contemporary educational literature. The results indicate a high overall level of commitment, particularly to personal, faith-based values such as sincerity, reliance on God, and ethical role modeling. In contrast, interactive and organizational principles—especially consultation (shūrā) and participatory decision-making—were applied at relatively lower levels. The study contributes original field-based insights by integrating an Islamic leadership framework into the analysis of female educational leadership in Yemen.